The incidence of vasovagal reactions during earlobe piercing - Xie, Zi-ao; Zhang, Kai-li; Han, Fang; Tang, Meng-yao; Chen, Jue-wei; Liu, Guang-peng (Frontiers in Medicine, 2023)
Background: Vasovagal reactions are common among patients with needle fear when receiving injection or venipuncture, but they are rarely studied in healthy people undergoing ear piercing. The purpose of this study was to evaluate the incidence and features of vasovagal reactions during the earlobe piercing. Methods: 1866 participants aged older than 13 years had their earlobes pierced in our department from January 2020 to January 2022. When the vasovagal reactions occurred in the procedure (e.g., dizziness, pallor, diaphoresis, and faintness, etc.), they were recorded and the more detailed demographic information of the participant was collected. Results: A total of 196 female cases with vasovagal reactions were reported of 1866 participants, including 58 who actually lost consciousness during earlobe piercing. The incidence of vasovagal reactions and vasovagal syncope was 10.5% and 3.11% respectively. People with syncopal reactions were all younger than 30 years. Conclusion: The vasovagal syncope is often very sudden and occurs without warning. The practitioners need to be familiar with these reactions, and prevent people from an unpredictable fall and subsequent injury during ear piercing.